The founding ideas of Ricardo Palma University - Ríos Burga, Jaime (2019)
This essay addresses and reconstructs the course of ideas that led to the founding of the Ricardo Palma University, from its inception through its different stages of construction, its institutional reform and future challenges. A university model based on the universality of knowledge, as a form of democracy with the aim of making humans more free, equal, caring and different beings. Founded on the basis of a new civil culture that surpasses all pragmatism.